Decreased levels of urinary di-2-ethylhexyl phthalate (DEHP) metabolites and biomarkers of oxidative stress in children exposed to DEHP-tainted foods in Taiwan in 2011: A 44-month follow-up. (November 2020) - Wu, Chia-Fang; Hsiung, Chao A.; Tsai, Hui-Ju; Cheng, Ching-Mei; Chen, Bai-Hsiun; Hu, Chiung-Wen; Huang, Yeou-Lih; Wu, Ming-Tsang
Abstract: A major health scandal involving DEHP-tainted (di-2-ethylhexyl phthalate) foodstuffs occurred in Taiwan in 2011. We investigated temporal relationships between urinary DEHP metabolites and biomarkers of oxidative stress in two cohorts of potentially affected children during that food scandal. One cohort was collected from Kaohsiung Medical University Hospital in southern Taiwan between May and June of 2011 (the KMUH cohort). This cohort was followed up at 2, 6, and 44 months. The other cohort was collected from a nationwide health survey conducted by Taiwan's National Health Research Institutes (the NHRI cohort) for potentially affected people between August 2012 and January 2013. Both cohorts only included children 10 years old and younger who had provided enough urine for analysis of urinary DEHP oxidative metabolites and two markers of oxidative stress: 8-oxo-2′-deoxyguanosine (8-OHdG) and malondialdehyde (MDA). The KMUH cohort had a simultaneous and significant decrease in urinary DEHP metabolites, 8-OHdG, and MDA, with the lowest concentrations found at the 6-month follow up and maintained until the 44-month follow up, consistent with those from NHRI cohort at ∼15–18 months post-scandal (p > 0.05). There were decreases in both DEHP metabolites and oxidative stress markers across the populations, but no association was observed between DEHP metabolites and oxidative stress markers in individuals in the two cohorts. Continued follow-up is needed to determine long-term health consequences in these children. Graphical abstract: Image 1 Highlights: A major health scandal involving DEHP-tainted foods occurred in Taiwan in 2011. The relation between DEHP toxicity and oxidative stress in children is unclear. A temporal change of urinary DEHP metabolites with oxidative stress was examined. Urinary DEHP metabolites and oxidative stress decreased after 44-month follow up.